Strategi Pembelajaran PAIKEMI pada Pembelajaran Pendidikan Agama Islam - Intan Sara; Annisa Desvita; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to describe the application of the PAIKEMI learning strategy in PAI learning. The application of the PAIKEMI learning strategy in Islamic Religious Education (PAI) aims to increase student achievement and engagement. This strategy focuses on student-centered learning, making learning active, innovative, creative, effective, fun and Islamic. In this research, the library research method was used. Data collection was carried out by utilizing library sources such as books, documents and journal articles. The research results show positive results in the implementation of PAIKEMI, which leads to increased cognitive competence and active participation of students. This strategy includes planning, implementation, factors that influence its effectiveness, and evaluation of student learning outcomes. By incorporating PAIKEMI into PAI classes, educators can create a more meaningful and enjoyable learning environment, fostering collaboration, creativity and effectiveness among students. This strategy includes approaches such as “Everyone Here is a Teacher”, which encourages active participation and individual engagement. Additionally, teachers undergo training and collaborative sessions to implement PAIKEMI effectively, ensuring successful lesson planning and student engagement.